The Emerging Role of Leptin Antagonist as Potential Therapeutic Option for Inflammatory Bowel Disease - Singh, Udai P. (2013)
Inflammatory bowel disease (IBD) is a chronic relapsing immune-mediated inflammatory disorder that affects millions of people around the world. Leptin is a satiety hormone produced primarily by adipose tissue and acts both centrally and peripherally. Leptin has been shown to play a major role in regulating metabolism, which increases during IBD progression. Leptin mediates several physiological functions including elevated blood pressure, tumorogenesis, cardiovascular pathologies and enhanced immune response in many autoimmune diseases. Recent development of a leptin mutant antagonist that blocks leptin activity raises great hope and opens up new possibilities for therapy in many autoimmune diseases including IBD. To this end, preliminary data from an ongoing study in our laboratory on pegylated leptin antagonist mutant L39A/D40A/F41A (PEG-MLA) treatment shows an inhibition of chronic colitis in IL-10(−/−) mice. PEG-MLA effectively attenuates the overall clinical scores, reverses colitis-associated pathogenesis including a decrease in body weight, and decreases systemic leptin level. PEG-MLA induces both central and peripheral leptin deficiency by mediating the cellular immune response. In summary, after blocking leptin activity, the correlative outcome between leptin-mediated cellular immune response, systemic leptin levels, and amount of adipose tissue together may provide new strategies for therapeutic intervention in autoimmune diseases, especially for intestinal inflammation.